2020
DOI: 10.1155/2020/7825413
|View full text |Cite
|
Sign up to set email alerts
|

Improving Grain Micronutrient Content of Durum Wheat (Triticum turgidum var. durum) through Agronomic Biofortification to Alleviate the Hidden Hunger

Abstract: Improvement of durum wheat grain quality through agronomic biofortification becomes a priority research area and an effective route to combat malnutrition. An experiment was conducted to evaluate the effect of micronutrient application to different varieties of durum wheat and seeding rate on final harvest grain quality under different growing locations. The treatments were arranged in split-split plot design where the varieties were assigned in the main plot, micronutrients into the subplots, and seeding rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Factors such as environmental conditions, soil nutrient availability, genetic variations, and other variables could all contribute to this variability [22,26,27]. The growing environment may have an impact on the uptake, translocation, and accumulation of mineral elements [12]. Similar to the current study, variability in mineral contents among different nger millet genotypes was reported in previous studies [21,23,28,29].…”
Section: Principal Component Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…Factors such as environmental conditions, soil nutrient availability, genetic variations, and other variables could all contribute to this variability [22,26,27]. The growing environment may have an impact on the uptake, translocation, and accumulation of mineral elements [12]. Similar to the current study, variability in mineral contents among different nger millet genotypes was reported in previous studies [21,23,28,29].…”
Section: Principal Component Analysissupporting
confidence: 80%
“…The contents of mineral elements in the nger millet landraces, including iron (Fe), zinc (Zn), manganese (Mn), copper (Cu), and chromium (Cr), were estimated using an atomic absorption spectrophotometer (Varian AA240FS) as described by Melash and Mengistu [12]. A dried seed sample of each landrace was ground to a ne powder, with 2 g of the powder placed in the ashing vessel and ashing was done at 550 o C. the resulting ash was then dissolved in a mixture of HCl-H 2 O (1:1) to complete the ashing process.…”
Section: Estimation Of Mineral Elementsmentioning
confidence: 99%
“…By understanding these allometric relationships, it may be possible to develop strategies that enhance both grain yield and nutritional quality, thereby meeting the future food and nutritional demands of a growing global population. In other studies, the foliar application of zinc sulfate has been widely acknowledged as an effective method for enhancing the mineral content of grains [ 12 , 13 ]. This implies that applying zinc sulfate to the leaves of durum wheat plants can be a beneficial approach to improve the mineral composition of the grains.…”
Section: Discussionmentioning
confidence: 99%
“…Integrated use of micronutrients coupled with optimum seeding rate and density-tolerant varieties has paramount importance to improve grain yield, protein content and grain micronutrient concentration, simultaneously [ 3 ]. This has been verified that the application of foliar-based zinc containing fertilizers (aka agronomic biofortification) during the crop growth period increases the grain mineral content [ 12 ], by about 3.04 mg kg −1 to 56.73 mg kg −1 of zinc [ 13 ]. Similarly, foliar application of iron containing fertilizers can be a practical approach to improving iron concentration, and quality in wheat grains [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The grain end-use functional properties are strongly associated with the storage protein contents and composition, which can be influenced either by agronomic like technologies [ 6 , 90 , 91 ], and environmental factors [ 8 , 92 ]. It is a function of total nitrogen uptake and partitioning of nitrogen and dry matter into the grain [ 93 ].…”
Section: Strategies Of Improving Grain End-use Functional Propertiesmentioning
confidence: 99%